2007
DOI: 10.1017/s0266467406003713
|View full text |Cite
|
Sign up to set email alerts
|

Root mycorrhizal colonization and plant responsiveness are related to root plasticity, soil fertility and successional status of native woody species in southern Brazil

Abstract: Twelve native woody species were studied to investigate the influences of soil fertility and root morphology on colonization by arbuscular mycorrhizal (AM) fungi during seedling establishment and growth. Seedlings were grown in soils of low and high natural fertility, uninoculated or inoculated with AM fungi, under greenhouse conditions. The mycorrhizal root colonization and plant responsiveness were higher among early successional species than late successional ones. Among early successional species, in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
0
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 29 publications
9
66
0
8
Order By: Relevance
“…In native woody species, mycorrhiza also decreased the specific root length and increased the root diameter (Zangaro et al, 2005(Zangaro et al, , 2007. The increase of the specific root length in the present work was…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…In native woody species, mycorrhiza also decreased the specific root length and increased the root diameter (Zangaro et al, 2005(Zangaro et al, , 2007. The increase of the specific root length in the present work was…”
Section: Resultssupporting
confidence: 65%
“…Mycorrhiza increased root hair incidence to values above 92% in the line lg40505-1 and the hybrid C333B. Conversely, previous reports showed reduction of root hair incidence in mycorrhizal maize (Bressan & Vasconcellos, 2002) and seedlings of native woody tropical trees (Zangaro et al, 2005(Zangaro et al, , 2007.…”
Section: Bacteriamentioning
confidence: 80%
“…Successfulness of mycorrhizal inoculation depends partially on the mycorrhizal dependency of each woody species (Siqueira & Saggin Junior 2001) which varies accordingly to the successional stage that a species belongs; pioneer and early successional species being more dependent compared to late successional and climax species (Carneiro et al 1996;Siqueira & Saggin-Júnior 2001;Zangaro et al 2007;Pasqualini et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies in Brazil have shown that nutrition and growth of native woody species are improved by the mycorrhizal association and that many species are moderate to very highly dependent on the association (Siqueira & Saggin Júnior 2001;Zangaro et al 2007). Despite this, mycorrhizal inoculation of seedlings under nursery conditions is not a common practice and no inoculant is available commercially.…”
Section: Introductionmentioning
confidence: 99%
“…The seasonal pattern of production and root length may be related to changes in organic matter accumulation (Cuevas and Medina 1988;Aerts et al 1992;Sundarapandian and Swany 1996), nutrient concentration in the soil (Maycock and Congdon 2000; Pregitzer et al 2000;Stewart 2000;Blair and Perfecto 2001), soil moisture (Hook et al 1994;Visalakshi 1994;Makkonen and Helmisaari 1999) and microbial activity (Zangaro et al 2007). …”
Section: Fine-root Morphologymentioning
confidence: 99%